Sistem Informasi Geografis untuk Pemetaan PT. Wifi Telkom di Kota Baturaja Berbasis Web - Aan Aidil Fitran yansa; Wijaya, Alpin; Rendy Juniar Dewa Alyaris; Alyaris, Dewa; Pujianto (Indo-MathEdu Intellectuals Journal, 2026)
The development of internet services in Baturaja City has increased in line with the community's need for fast and stable access to information. PT WiFi Telkom, as one of the internet service providers, continues to expand its network and add access points in various areas. However, limited information about WiFi location points, service coverage areas, and supporting facilities has made it difficult for the community to access services optimally. This study aims to design and develop a web-based Geographic Information System (GIS) used to map the PT WiFi Telkom network in Baturaja City. The system development method used is the Waterfall method, which includes the stages of requirements analysis, system design, implementation, and testing. The system was built using digital maps to display spatial information in the form of WiFi hotspot locations, service coverage areas, and other supporting information. The results of the study show that the web-based GIS developed is capable of presenting PT WiFi Telkom service location information accurately, easily accessible, and interactively, thereby helping the community find the nearest WiFi hotspots and supporting service providers in managing their networks more effectively